Joint stiffness of cold-formed steel pallet rack connections: a comparison of the methodology - Mohan, Vimal; Vishnu, C.R. (Journal of Structural Engineering, 2024)
Industrial pallet rack systems are made up of three dimensional structural arrangement using cold-formed steel members. The rack columns (upright) have perforations at prescribed intervals to facilitate the assemblage of beams with end connectors. Tabs are used in connections due to which the joints are highly semi-rigid in nature. The diversity in the difference of stiffness and strength of connecting member makes, it is almost impossible to develop a generalised model for analytical prediction. This paper describes the beam-column connection tests carried out on a commercially available pallet rack system by adopting single cantilever test set-up. Five sets of combinations are identified based on variation in beam depth and number of tab connectors to study the connection flexibility. Three tests were performed for each set to bring in uniformity in the result taking the total number of tests to 15. Experiments conducted on steel end connectors and the results showed that a greater stiffness in the connection is achieved using connectors with more number of tabs and greater depth of the beam. A comparative study on arriving at the joint stiffness using the three different methods like the initial stiffness method, slope to half ultimate method and the equal area method is carried out. The calculation of joint stiffness by means of initial stiffness method is considered to overestimate the values when compared to the other two methods. Equal area method is concluded to be the most appropriate method in arriving at the joint stiffness of any pallet rack connection, due to its low variance arrived in the set population.